Diving behaviour of Atlantic salmon at sea: effects of light regimes and temperature stratification - Hedger, Richard David; Rikardsen, Audun H.; Strøm, John Fredrik; Righton, David A.; Thorstad, Eva Bonsak; Næsje, Tor (Marine Ecology Progress Series, 2017)
Accepted manuscript version. Published version available in Marine Ecology Progress Series, 2017;574:127-140 The diving behaviour of adult Atlantic salmon Salmo salar L. post-spawners in the Norwegian and Barents Seas was monitored with pop-up satellite archival tags (PSATs) and data storage tags (DSTs). Salmon from the 3 studied populations showed similar depth use patterns: tagged specimens spent most of their time near the surface (mean of 82% of the time at depths <10 m), with occasional short deep dives (>200 m depth, median time = 2.31 h; range = 0.18 to 22.5 h), the deepest recorded being 707 m. Increased use of greater depths occurred during daytime than night-time in the months between polar day and polar night (August to October). Diel change in depth use around the time of polar night (November to January) was weakest for the population (from the River Alta) that migrated furthest north. Diving was more frequent and shallower when the mixed layer was near the surface during the months of June to October. There was an increase in diving depth (>200 m) when the mixed layer extended to ~200 or 300 m in winter and spring (December to April). Deep diving consisted of ‘U’ shaped dives, possibly indicative of foraging. We hypothesise that seasonal light conditions, dependent on geographical location, affect Atlantic salmon diving, and that changes in diving depth may be due to seasonal differences in prey aggregation.